Odpowiedzi

2010-01-05T16:45:15+01:00
X+y=2
y-2x=3

x=2-y
y-(2-y)=3

x=2-y
y-2+y=3

x=2-y
2y=5 ----> y=2,5

x= -0,5
y=2,5

--------------------------------------------------------------
x+y=4
y-2x=-2

y=4-x
4-x-2x=-2 ---->-3x=-6 -----------> x=2

y=2
x=2



Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-01-05T16:45:46+01:00
X+y=2
y-2x=3

x=2-y
y-(2-y)=3

x=2-y
y-2+y=3

x=2-y
2y=5
y=2,5

x= -0,5
y=2,5



x+y=4 |*(-1)
y-2x=-2

-x-y=-4
y-2x=-2

-3x=-6
x=2

x+y=4
2+y=4
y=2
2010-01-05T17:02:00+01:00

x=4-y
y-2(4-y)=-2

x=4-y
y-8+2y=-2

x=4-y
3y= -2+8

x=4-y
3y=6/ :3

x=4-y
y=2

x=4-2
y=2

x=2
y=2